A Comprehensive Review on the Economic Status of the Global Convenience Food Industry - Banerjee, Swapan (International Journal of Business, Management and Economics, 2021)
Nowadays, people worldwide are leading to fast lifestyles due to their official work and childrens’ education. The situations compel almost every earning member who does not have enough time to buy fresh vegetables and other essential food ingredients for cooking good foods both in the lunch and dinner at home. For the last two decades, mainly office goers are dependent on convenience foods called ready-to-eat foods. Disposable income, taste preferences, working stress, and psychological tenacity are the significant factors of the growing demand for fast food or ready meals among the middle-class urban population. Recent trend shows that the global convenience food market is expected to reach a 4.4% compound annual growth rate at the end of 2025. India is also supposed to be a significant contributor among other developed countries. The country is expected to reach the compound annual growth rate (CAGR) tentatively 17%-19% (approximately $655 million) by 2025. Small-scale industries (SSI) play significant roles by engaging themselves with excellent investment in the convenience food market. The increasing demand for food products is the main reason sourced from the millions of consumers worldwide. Hence